Model Jurisprudential Inquiry Learning Berbasis STEAM Untuk Kewarganegaraan Digital Siswa - Zaenul Slam; Lu’luil Maknun; Haura Difa Assobiah (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2026)
This study aims to develop a conceptual model Jurisprudential Inquiry learning berbasis Science, Technology, Engineering, Art, and Mathematics (STEAM-JIL), describe students' perceptions of the implementation of the model and students' digital citizenship, and test the effectiveness of the model on the development of students' digital citizenship. This study used a mixed methods approach and involved three teachers, 192 students from junior high schools in Majalengka Regency, West Java Province, Indonesia, and three lecturers of Civic Education as research samples. Data were collected through various methods, including observation, interviews, focus group discussions, questionnaires, and attitude scales. The collected data were analyzed using interactive qualitative analysis, descriptive statistical analysis, and t-tests. The findings of this study are as follows: (1) STEAM-JIL is characterized by the application of STEAM education principles, integration of digital citizenship materials, and the existence of a diversity of value-based learning models, science, and contextual learning; (2) Perceptions of STEAM-JIL model are in the